Differential regulation of the N-myc proto-oncogene by ROR alpha and RVR, two orphan members of the superfamily of nuclear hormone receptors. - Dussault, I (1997)
ROR alpha1 and RVR are orphan members of the superfamily of nuclear hormone receptors which constitutively activate and repress, respectively, gene transcription by binding to a common DNA sequence. In an attempt to understand the physiological functions of these two transcription factors, we aimed to identify target genes. We have identified a consensus binding site for ROR alpha1 and RVR in the first intron of the N-myc gene that we designated N-myc RORE (ROR response element). Unlike most of the intronic sequence, the region encompassing the N-myc RORE is highly conserved between human and mouse, underscoring its importance. Our studies revealed that ROR alpha1 and RVR specifically bind to the human and mouse N-myc ROREs and transactivate and transrepress, respectively, reporter constructs containing the ROREs. Moreover, Northern blot analysis demonstrated a direct modulation of an exogenously introduced N-myc gene by ROR alpha1 and RVR in COS-1 cells. This effect is mediated through the N-myc RORE, since mutation of this site abolished the regulatory effects of both receptors. While transfection of ROR alpha1 in P19 embryonic carcinoma cells had no effect on the levels of endogenous N-myc mRNA, RVR down-regulated its expression. The regulatory function of the N-myc RORE was further demonstrated by the rat embryonic fibroblast (REF) transformation assay. Mutation of the RORE increased the oncogenic potential of the N-myc gene in the REF assay. The foci were more numerous and significantly larger with the mutated than with the wild-type N-myc gene, regardless of ROR alpha1 or RVR expression. Moreover, concomitant expression of ROR alpha1 and wild-type N-myc resulted in a twofold increase in the number of transformed foci. In contrast, RVR expression resulted in the formation of foci that could be established as permanent clones with a very low frequency compared to foci transformed in its absence. These observations show that ablation of the RORE results in a more oncogenic form of N-myc and suggest that deregulation of the activity of the ROR alpha1 and RVR could contribute to the initiation and progression of certain neoplasias.